2020
DOI: 10.1186/s40981-020-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

Perianesthetic death: a 10-year retrospective observational study in a Japanese university hospital

Abstract: Background: Studies reporting on perianesthetic death and anesthesia-related death are limited. The present study aimed to assess the incidence of perianesthetic death and its relation to anesthesia and to describe the patient characteristics and main events leading to death in cases of anesthesia-related death and anesthesia-contributory death. Methods: We conducted a retrospective chart review of patients in whom anesthesia procedures were performed by anesthesiologists at a Japanese tertiary hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A study with 785,467 patients who underwent general anaesthesia demonstrated a death rate attributed solely to anaesthesia of 0.0005% [25]. Another recent study in Japan including 46,378 patients under general anaesthesia reported that none of 41 peri-anaesthetic deaths were caused exclusively by anaesthesia, though but in ten cases anaesthesia was a contributing factor (0.022%) [26]. These considerably lower mortality rates render obvious the gap between medical and veterinary anaesthesia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study with 785,467 patients who underwent general anaesthesia demonstrated a death rate attributed solely to anaesthesia of 0.0005% [25]. Another recent study in Japan including 46,378 patients under general anaesthesia reported that none of 41 peri-anaesthetic deaths were caused exclusively by anaesthesia, though but in ten cases anaesthesia was a contributing factor (0.022%) [26]. These considerably lower mortality rates render obvious the gap between medical and veterinary anaesthesia.…”
Section: Introductionmentioning
confidence: 98%
“…It should be noted that in the human literature expert committees revise and analyse patients' documents and categorise anaesthesia-related deaths according to the causative factor (anaesthesia, procedure, underlying pathology, equipment failure, etc. ), distinguishing peri-anaesthetic deaths between those in which anaesthesia was the definite cause and those in which anaesthesia was a contributing factor [25,26,29]. This extensive classification is unfortunately not the case in the veterinary literature, and as a result the anaesthesia-related mortality rates where anaesthesia was the main cause of death may not reflect the true values.…”
Section: Introductionmentioning
confidence: 99%